2009
DOI: 10.1590/s0044-59672009000200016
|View full text |Cite
|
Sign up to set email alerts
|

Atividade inseticida do óleo essencial de pimenta longa (Piper hispidinervum C. DC.) sobre lagarta-do-cartucho do milho Spodoptera frugiperda (J. E. Smith, 1797) (Lepidoptera: Noctuidae)

Abstract: RESUMOOs objetivos desta pesquisa foram a obtenção e caracterização do óleo essencial de folhas de pimenta longa Piper hispidinervum, e avaliação de seu efeito no comportamento e/ou mortalidade da lagarta-do-cartucho do milho Spodoptera frugiperda. O óleo essencial foi obtido pela técnica "arraste a vapor d'água", utilizando-se de um aparelho de Clevenger modificado, e posteriormente submetido, à análise por CG-EM e CG. Foram realizados testes de ingestão e contato tópico em lagartas de 1° e 3° ínstar. Os resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
20
0
17

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(40 citation statements)
references
References 24 publications
1
20
0
17
Order By: Relevance
“…Among the compounds that are synthesized by the secondary metabolism of plants, terpenoids are a rich source of bioactive molecules that exhibit toxicity to various pests (Ali et al, 2010;Lima et al, 2013;Lima et al, 2009;Silva et al, 2010). Some studies have shown that these compounds act as inhibitors of AChE, impair oviposition (Alexenizer;Dorn, 2007;Cavalcante;Vasconcelos, 2006) and cellular respiration (Yu, 2008) and act as synergists of other bioactive agents (Fazolin et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Among the compounds that are synthesized by the secondary metabolism of plants, terpenoids are a rich source of bioactive molecules that exhibit toxicity to various pests (Ali et al, 2010;Lima et al, 2013;Lima et al, 2009;Silva et al, 2010). Some studies have shown that these compounds act as inhibitors of AChE, impair oviposition (Alexenizer;Dorn, 2007;Cavalcante;Vasconcelos, 2006) and cellular respiration (Yu, 2008) and act as synergists of other bioactive agents (Fazolin et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…[43] evaluated the insecticidal activity of the essential oil of P. hispidinervum, collected in Lavras in the state of Minas Gerais, on Spodoptera frugiperda (Fall armyworm), atributing the efect to safrole (82%), the major component of the essential oil being analyzed. The essential oil of Piper betle showed insecticidal activity by inhibiting the development of Spodoptera litura pupae without causing damage to the Eudrilus eugeniae organism [56].…”
Section: Biological Activities Of Essential Oils Of the Piper Speciesmentioning
confidence: 99%
“…O anis-estrelado, Illicium verum Hook. F. (Schisandraceae), é muito utilizado como condimento e cosmético, podendo conter como constituinte majoritário o (E)-anetol, o qual possui ação fungicida contra dermatófitos (Kosalec et al, 2005 O processo de obtenção dos óleos essenciais foi o de hidrodestilação por meio de um aparelho de Clevenger modificado, com duração de 2,5 horas, pelo qual o hidrolato obtido foi centrifugado a 965 g a 25 o C, durante 5 minutos, para promover a separação entre as fases aquosa e oleosa, sendo esta última coletada e armazenada em frasco de vidro âmbar a 4 o C até a realização das análises posteriores (Lima et al, 2009).…”
Section: Introductionunclassified